Intravoxel incoherent motion (IVIM) MRI: principles and applications - Le Bihan, Denis (Pan Stanford Publishing, 2018)
Cover -- Half Title -- Title -- Copyrights -- Dedication -- Contents -- Foreword -- Preface -- Section I Introduction to IVIM MRI -- Chapter 1. Introduction to IVIM MRI Denis Le Bihan -- 1.1 The IVIM Concept -- 1.1.1 Molecular Diffusion -- 1.1.2 Perfusion-Driven Pseudodiffusion -- 1.1.3 Other Sources of IVIM -- 1.2 IVIM MRI -- 1.2.1 IVIM Contribution to the MRI Signal -- 1.2.2 Extracting Diffusion and Perfusion Parameters -- 1.3 Pitfalls to Consider for an Accurate Estimation of Perfusion-Driven IVIM Parameters -- 1.3.1 Non-Gaussian Tissue Diffusion -- 1.3.2 Rician Noise -- 1.3.3 Erratic Signals -- 1.4 Perfusion-Driven IVIM MRI and "Classical" Perfusion -- 1.4.1 IVIM MRI Reflects Capillary Network Architecture and Blood Flow -- 1.4.2 Link with Tracer-Perfusion Methods -- 1.5 Non-perfusion-Driven IVIM MRI -- 1.6 Conclusion -- Section II Other MRI Approaches toPerfusion Imaging -- Chapter 2. Other MRI Approaches to Perfusion Imaging (ASL, DSC, DCE) Emmanuel L. Barbier, Sylvie Grand, Alexandre Krainik, and Jan M. Warnking -- 2.1 The Perfusion Parameters: The Microvascular Network and Physiological Principles -- 2.2 Perfusion Tracers -- 2.3 Biophysical Modeling of Nondiffusible Tracers -- 2.3.1 Dynamic Approach -- 2.3.2 Steady-State Approach -- 2.4 Biophysical Modeling of Diffusible Tracers -- 2.5 Exogenous Tracers: DSC, Steady-State Approaches, and DCE -- 2.5.1 Impact of Exogenous Tracers on the MR Signal -- 2.5.2 Dynamic Susceptibility Contrast MRI -- 2.5.3 Steady-State Susceptibility MRI -- 2.5.4 Dynamic Contrast-Enhanced MRI -- 2.6 Endogenous Tracer: Arterial Spin Labeling -- 2.6.1 ASL MRI Sequences -- 2.6.2 Analyzing the ASL Signal -- 2.6.3 Applications of ASL -- 2.7 Conclusion -- Section III Clinical Applications of IVIM MRI Part 1: Neurological Applications -- Chapter 3. Clinical Applications of IVIM MRI to the Nervous System C. Federau